Direct synthesis of all-inorganic heterostructured CdSe/CdS QDs in aqueous solution for improved photocatalytic hydrogen generation. Issue 21 (12th May 2017) - Li, Zhi-Jun; Fan, Xiang-Bing; Li, Xu-Bing; Li, Jia-Xin; Zhan, Fei; Tao, Ye; Zhang, Xiaoyi; Kong, Qing-Yu; Zhao, Ning-Jiu; Zhang, Jian-Ping; Ye, Chen; Gao, Yu-Ji; et al.
Abstract : A facile aqueous approach is developed to synthesize heterostructured CdSe/CdS QDs for advanced hydrogen photosynthesis. Abstract : Here we present a facile aqueous approach to synthesize heterostructured CdSe/CdS QDs with all-inorganic chalcogenide S 2− ligands under mild conditions. High-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), and steady-state emission spectroscopy demonstrate that the heterostructured CdSe/CdS QDs with sulfur-rich surface composition are formed by heterogeneous nucleation of Cd 2+ and S 2− precursors on the CdSe QDs. After adsorption of small Ni(OH)2 clusters over the surface in situ, the CdSe/CdS–Ni(OH)2 photocatalyst enables H2 production efficiently with an internal quantum yield of 52% under visible light irradiation at 455 nm, up to an 8-fold increase of activity to that of spherical CdSe QDs–Ni(OH)2 under the same conditions. Femtosecond transient absorption spectroscopy, X-ray transient absorption (XTA) spectroscopy, steady-state and time-resolved emission spectroscopy show that the quasi-type-II band alignment in the CdSe/CdS heterostructure is responsible for the efficiency enhancement of light harvesting and surface/interfacial charge separation in solar energy conversion. The unprecedented results exemplify an easily accessible pattern of aqueous synthesis of all-inorganic heterostructured QDs for advanced photosynthetic H2 evolution.